Activation Control System in Motorized Vehicles Using the Global Positioning System (GPS) - Aris Budiyarto; Abdur Rohman Harits Martawireja; Mohammad Harry Khomas Saputra; Gun Gun Maulana (Universitas Negeri Medan, 2023)
In Indonesia, the theft rate is still quite high. According to Bappeda data, cases of theft still tend to be high. In 2019, there were 362,000 cases of theft. CCTV use is still ineffective because at the time of the theft of goods, we only know the goods taken and the perpetrators. In order to catch the perpetrators and return the goods, it is necessary to process them first and find the location of the perpetrators themselves. Therefore, we propose an idea entitled